Local Sustainability Assessment of the Wonogiri Multipurpose Reservoir Catchment Area in Central Java Province, Indonesia - Bunga Ludmila Rendrarpoetri; Ernan Rustadi; Akhmad Fauzi; Andrea Emma Pravitasari (Land)
The sustainability of watershed management is a crucial issue that must be addressed to guarantee the persistence of watershed services including agriculture, food production, and energy supply. This issue has also been addressed in Presidential Regulation No. 18/2020 concerning the National Medium-Term Development Plans for 2020–2024, which stipulate the restoration of priority watersheds, including the Upstream Bengawan Solo Watershed. This study seeks to address this information gap by assessing the local sustainability of the watershed from a temporal dynamics perspective by calculating the Local Sustainability Index (LSI), Local Moran Index, and spatial associations. Measuring sustainable development indices locally is essential because each location has different characteristics, and using specific indicators at the local level is rarely done. The enactment of the national law on village autonomy in Indonesia necessitates the formulation of sustainable development indicators at the village level. These indicators serve as the metrics and frameworks for local government policies and initiatives. Our results show that village sustainability in the social and economic dimensions has increased from 2007 to 2021, especially in urban activity center areas that serve social and economic facilities. This seems different in the environmental dimension, where the sustainability value decreased from 2007 to 2021. The concentration of low sustainability values on ecological conditions occurred in pocket areas. Environmental problems were indicated by land-use conversion and disaster areas.